Negative magnetoresistance in indium antimonide whiskers doped with tin - Druzhinin, A.; Ostrovskii, I.; Khoverko, Yu.; Liakh-Kaguy, N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
Negative magnetoresistance of InSb whiskers with different impurity concentrations 4.4⋅1016 –7.16⋅1017 сm–3was studied in longitudinal magnetic field 0–14 T in the temperature range 4.2–77 K. The negative magnetoresistance reaches about 50% for InSb whiskers with impurity concentration in the vicinity to the metal–insulator transition. The negative magnetoresistance decreases to 35 and 25% for crystals with Sn concentration from the metal and dielectric side of the transition. The longitudinal magnetoresistance twice crosses the axis of the magnetic field induction for the lightly doped crystals. The behavior of the negative magnetoresistance could be ex-plained by the existence of classical size effect, in particular boundary scattering in the subsurface whisker layer.